A COMPARISON OF THE FREQUENCIES OF THE 1S-2S AND 2S-4P TRANSITIONS IN ATOMIC-HYDROGEN - Thompson, C; Woodman, G; Foot, C; Hannaford, P; Stacey, D; Woodgate, G (1992)
The difference between the frequency of the 2S-4P 1/2 transition and a quarter of the 1S-2S transition frequency in atomic hydrogen has been measured by high-resolution laser spectroscopy. The result is 4696.3 (2.0) MHz, from which the value 8168 (8) MHz is derived for the 1S Lamb shift. This is the first determination of this quantity from continuous wave spectroscopy without frequency standards. © 1991 IOP Publishing Ltd.